Pseudowuiessa, a new genus of brachypterous Mezirinae (Hemiptera: Heteroptera: Aradidae) from China - Shi, Kai; Bai, Xiaoshuan; Wu, Zhiyi; Heiss, Ernst; Cai, Wanzhi (Zootaxa, 2016)
A new brachypterous flat bug (Hemiptera: Heteroptera: Aradidae) genus and species, Pseudowuiessa producta Bai, Heiss & Cai, gen. nov. & sp. nov., is described from Yunnan, China. A key to related genera is given and the diagnostic characters of the new taxon are illustrated.